In vitro study on how cold plasma affects dentin surface characteristics - Strazzi-Sahyon, Henrico Badaoui [UNESP]; Suzuki, Thaís Yumi Umeda; Lima, Glívia Queiroz [UNESP]; Delben, Juliana Aparecida; Cadorin, Bruno Mena; Nascimento, Vanessa do; Duarte, Simone; Santos, Paulo Henrique dos [UNESP] (Elsevier, 2021)
Purpose: Studies evaluating different features of cold plasma action on dentin surface characteristics are lacking. Thus, this in vitro study aimed to determine the effect of cold plasma under different protocols of exposure time, distance to plasma source, and the association of argon gas with distinct concentrations of oxygen on the wettability, surface energy, total free interaction energy, surface roughness, morphology and chemical composition of dentin. Material and methods: One hundred and twenty-five bovine dentin samples were used and divided into twenty-five groups according to the exposure time to plasma (15, 30, or 60 s); distance between plasma source and dentin surface (3 or 6 mm); argon gas without plasma generation; and plasma generated by argon gas and association of argon gas with distinct concentrations of oxygen (2 % or 3 %) (n = 5). Contact angle (θ), surface energy (γs) and total free interaction energy (ΔG) were measured using a goniometer (Krüss), while surface roughness (Ra) was evaluated by a profilometer (Mitutoyo). Representative samples were submitted to scanning electron microscopy (JEOL) to ilustrate the morphology and chemical composition of dentin. Data comparing control group with all experimental groups were submitted to ANOVA followed by Tukey's test (α = .05). Data comparing oxygen gas action at different concentrations and argon gas on dentin characteristics were submitted to non-parametric Kruskal–Wallis test, followed by Dunn test for comparison between the groups and methods (α = 0.05). Results: In general, argon gas without plasma generation promoted no significant difference on dentin surface characteristics compared to control group (P > .05), differently for the cold plasma that significantly reduced contact angle values and increased total free interaction energy of dentin surface (P < .05). Overall, feeding of oxygen at distinct concentrations promoted significant difference on dentin surface characteristics compared to control group (P < .05). Exposure time and distance protocols interfered with contact angle, surface energy and total free interaction energy analyses for each gas. There was no significant difference on surface roughness (P > .05), morphology and chemical composition of dentin submitted to argon gas, cold plasma, and distinct concentrations of oxygen. Conclusion: In conclusion, plasma generated by argon gas and its feeding with 2 % and 3 % oxygen gas improved the dentin surface characteristics about wettability, surface energy and total free interaction energy. Such treatments preserved the surface roughness, morphology and chemical composition of dentin. The protocols of groups Ar-6mm-15sec, ArO2-3mm-30sec and ArO3-3mm-15sec are recommended for improvement of dentin surface characteristics.
Keywords: Argon; Dentin; Oxygen; Plasma; Surface properties; Wettability